Relacje między teorią a praktyką budżetowania w Polsce w aspekcie standardów edukacyjnych rachunkowości - Krysik, Małgorzata (Relations between the Theory and the Practice of Budgeting in Poland From Aspect of Education Standards of Accounting, 2005)
There are many differences between the theory and solutions used in the practice in the field of budgeting. The author showed the areas of no suitable relations between the theory and the practice of budgeting and the reasons of existing them. This was shown by presenting the investigation of the author conducting in Polish enterprises. There is the analysis of relations in areas of links between the planning and the budgeting, methods of preparing budgets, the system of the budgeting, the structure of the master budget, links between the cost accounting and presenting cost information in the master budget, using the budget as a tool of control, motivating and evaluation of employees. Differences between the theory and the practice often result from unknowing and misunderstanding general methodology of the budgeting and this is the main reason why the education should focus on them. New worldwide and Polish innovative solutions should be implemented to the education standards.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 268-275